IMPROVING SPEAKING SKILLS THROUGH FLASH CARDS AT "BE SELF" ENGLISH COMMUNITY IN PACIRAN LAMONGAN - Farokhah, Fiqih Aisyatul; Latifah, Eny (Jurnal Pengabdian Masyarakat Berkarya, 2024)
This community service activity is designed to enhance the English language proficiency of members of the "Be Self" learning community in Paciran, Lamongan through the utilization of flash card learning media. The impetus for this initiative stems from the prevalent challenges encountered by English language learners in the region, namely a dearth of confidence, inadequate oral practice, and a paucity of engaging and applicable learning materials. The approach employed in this activity is a participatory one, utilizing interactive training that involves the provision of material, the demonstration of the use of flash cards, paired practice, and reflection sessions. The implementation of the activity was divided into several sessions, each of which was designed to cultivate participants’ courage in using English orally in a conducive learning atmosphere. The findings of the activity demonstrated that the utilization of flash cards enhanced the participants’ level of activity, confidence, and capacity to comprehend and employ English vocabulary in basic sentences. Furthermore, the participants exhibited a notable degree of enthusiasm for the method employed.